Penyuluhan Pemberian Probiotik Bioplus Terhadap Performa Domba di Kelompok Wanita Tani Sauyunan - Mutia Sari; Kenedy Putra; Lilis Riyanti (Jurnal Penyuluhan Pertanian, 2022)
The population of sheep in Kaso Village, Tambaksari District is still very low compared to the average number of needs each year. One of the feed manipulation techniques that can be done is by giving Bioplus probiotics. This study aims to analyze the increase in knowledge and skills of farmers on the provision of Bioplus probiotics. This study aims to analyze the improvement of farmers' knowledge and skills on the provision of Bioplus probiotics The extension technique used uses a combination of media and extension methods such as lectures, discussions, demonstrations of methods, and applied studies and is combined with powerpoint media and posters. The instrument used is a questionnaire that has been tested for validity and reliability using SPSS version 21. The counseling respondents consisted of 30 members of KWT Sauyunan. The evaluation of the extension was analyzed using the Padmowiharjo formula (1999). The results of the extension evaluation show the criteria of Success for the knowledge aspect and Fairly Successful in the skill aspect. Thus the extension of the provision of Bioplus probiotics to sheep is able to increase the knowledge and skills of members of the women's farmer group.